Attitude in the Second 2024 US Presidential Debate : An Appraisal Analysis of Donald Trump’s Use of Inscribed and Invoked Attitude - Johansson, Ronja (My University, 2025)
This paper examines Donald Trump’s use of attitudinal meanings in the second 2024 US presidential debate. The study applies the Appraisal framework, developed by Martin and White. The scope of examination is limited to Attitude, a semantic subsystem of appraisal. Attitude deals with positive and negative evaluative meanings, and is effective tool for analysing election discourse because candidates may use negative evaluation of the opponent and positive appraisal of self. The purpose of this paper is to analyse Donald Trump’s use of attitudinal meanings to examine how they may persuade the audience and change public perceptions. The selected data are examined to identify and categorise attitudinal meanings into three subtypes of attitude: affect, judgement, and appreciation, as well as their subcategories. This thesis identifies and analyses the layers of explicit and implicit attitude in the selected data, illustrates the complexity of attitudinal meanings, and discusses possible interpretations of the instances in different contexts.
Keywords: evaluation, appraisal, attitude, discourse analysis, political, Donald Trump